Juvenile Xanthogranuloma as Differential Diagnosis of a Vulvar Mass: A Case Report - Bada Bosch, Isabel; Cañizo, Agustín del; Campos-Domínguez, Minia; Ordoñez, Javier; Blanco Verdú, María Dolores; Fanjul, María; Pérez-Egido, Laura; de Agustín, Juan Carlos (European Journal of Pediatric Surgery Reports, 2022)
Vulvar masses in children are an unusual finding but their differential diagnosis is extensive. In case of solid masses, rhabdomyosarcoma (RMS) must always be considered due to the fact that it is the most common tumor in external genitals during childhood. However, RMS has a radiological appearance very similar to juvenile xanthogranuloma (JXG). We present a 16-month-old girl with a 2 cm solid mass on her left labia majora, with four overlying cutaneous papules. After imaging tests, an excisional biopsy was programmed due to high malignancy suspicion. Histopathology of the mass and one of the papules was diagnostic for JXG. After a 12-month follow-up, the patient shows no signs of relapse or complication. Deep JXG is an uncommon entity in childhood and exceptional in the genital area. Therefore, it must be included in the differential diagnosis of a solid vulvar mass, especially if accompanying yellowish xanthomatous cutaneous lesions are present.
Keywords: vulvar mass; juvenile xanthogranuloma; rhabdomyosarcoma